Marine radiocarbon resservoir effect of coastal waters off Cape Verde Archipelago - Soares, António (2011)
Quantification of the marine radiocarbon reservoir effect (R) is essential in order to calibrate conventional 14C dates from marine shell samples with reliability. R also provides information concerning the intensity of coastal upwelling in marine regions influenced by this phenomenon. 14C ages of closely associated marine samples (mollusk shells) and terrestrial samples (goat bones) from São Vicente Island, Cape Verde Archipelago, permitted the first calculation of the marine 14C reservoir effect in this region. A R weighted mean value of 70 ± 70 14C yr was obtained. This value is in accordance with the previously published oceanographic conditions of the region indicating the existence of a seasonal active upwelling regime.